Meaning Analysis on Protect of Earth Poster: Denotative and Connotative Analysis - Hasbullah, Hasbullah; Syamsurrijal; Ananda , Desti (Jurnal Ilmu Sosial dan Humaniora, 2023)
Posters are generally used as a medium to convey messages that are visually and creatively designed according to needs. Poster media are categorized as outdoor media, the function of which is to attract the attention of the public to see or read the messages they contain. Many types of poster themes found in society are invitations, appeals, prohibitions and commercial properties. The elements of invitation, appeal and prohibition are usually found in posters that emphasize environmental protection, health and others. Posters about protecting the environment or the earth are often seen on social media. Through attractive and creative displays, these posters have unique visuals and use soft colors. However, from a soft visual appearance, what messages can make people aware of the importance of protecting the environment or our earth? The purpose of this study is to analyze the meaning of the Protect the Earth posters that often appear on social media brands. Through a qualitative approach and based on the semiotic theory of Rolan Barthes, this research produces a visual denotation meaning of the shape of a tree still growing, a tree cut down and a symbol of two hands carrying seeds and soft colors. In connotation, the meaning conveyed by the poster invites all the audiences to take care of the importance of protecting our earth from the evil hands that destroy trees wildly.  The implication of this research is to gently educate about our concern for the surrounding nature.